Metalacurbs foordi sp. nov., a new Lacurbsinae (Opiliones, Laniatores, Biantidae) from Ankasa National Park, Ghana - Pérez González, Abel (2024)
Despite being one of the most conspicuous African opilionids, the members of Lacurbsinae remain one of the least known groups of harvestmen species. All eight previously known species of Lacurbsinae are inadequately described and poorly illustrated, leaving the morphological characteristics of this subfamily obscure. After more than half a century, we describe a new species of Lacurbsinae. Metalacurbs foordi sp. nov. is described based on a male specimen collected in Ankasa National Park, Ghana, with a detailed description and illustration of its external and genital morphology. This marks the first modern taxonomic description of a species within Lacurbsinae, including an illustration and description of the male genital morphology, a crucial modern taxonomic characteristic for Opiliones, and represents a starting point for the taxonomic revision of the subfamily.